HELLP Syndrome with Long-Lasting Severe Sepsis: A Case Report (Annals of Medical Research, 2021)
None
Keywords: Pre-eclampsia; HELLP Syndrome; Maternal Morbidity And Mortality; Sepsis; Thrombocytopenia.